Standardized Nutrition Care Process for Patients with Postoperative Cancer Pain Intra-Abdominal Tumors with Malnutrition : Case Study - Aisyah, Siti; Winda Rizki Pebrina Batubara (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Cancer is one of the leading causes of cancer deaths worldwide. Cancer patients often experience decreased food intake and poor nutritional status due to pain, nausea, vomiting, and the effects of chemotherapy and surgery. This case study aims to determine the implementation of the Standardized Nutrition Care Process (PAGT) in patients with post-operative cancer pain from an intra-abdominal tumor suspected of being a rectosigmoid mass, pre-chemotherapy, and malnutrition. The case study was conducted in May 2023 at Dr. Moewardi General Hospital in Surakarta. Data were obtained through interviews, observations, anthropometric measurements, biochemical examinations, and medical records. PAGT was carried out through the stages of assessment, diagnosis, intervention, monitoring, and nutritional evaluation. The patient was a 48-year-old woman who had experienced a 26% weight loss in the last 3 months with a BMI of 16.17 kg/m² and a waist circumference of 20.6 cm (malnutrition). Biochemical results showed anemia (Hb 11.5 g/dL). Energy and protein intake were far below requirements. Nutritional diagnoses established included: energy-protein malnutrition, inadequate oral intake, and risk of micronutrient deficiency. Interventions included a high-energy-protein diet and low residue diet with texture modifications and nutritional counseling. Monitoring showed improvement in intake, although it still did not meet requirements. The conclusion is PAGT in patients with intra-abdominal cancer and malnutrition can help identify nutritional problems and plan appropriate dietary interventions. Appropriate nutritional interventions are crucial to prevent worsening nutritional status and support the success of medical therapy.